Updating the therapeutic role of ginsenosides in breast cancer: a bibliometrics study to an in-depth review - Deng, Xianguang; Wang, Juan; Lu, Chenyi; Zhou, Yao; Shen, Lele; Ge, Anqi; Fan, Hongqiao; Liu, Lifang (Frontiers in Pharmacology, 2023)
Breast cancer is currently the most common malignancy and has a high mortality rate. Ginsenosides, the primary bioactive constituents of ginseng, have been shown to be highly effective against breast cancer both in vitro and in vivo. This study aims to comprehensively understand the mechanisms underlying the antineoplastic effects of ginsenosides on breast cancer. Through meticulous bibliometric analysis and an exhaustive review of pertinent research, we explore and summarize the mechanism of action of ginsenosides in treating breast cancer, including inducing apoptosis, autophagy, inhibiting epithelial-mesenchymal transition and metastasis, and regulating miRNA and lncRNA. This scholarly endeavor not only provides novel prospects for the application of ginsenosides in the treatment of breast cancer but also suggests future research directions for researchers.